PENGARUH PENERAPAN MEDIA STRIP STORY TERHADAP PENINGKATAN MOTIVASI BELAJAR BAHASA ARAB SISWA SMPN 1 HILIRAN GUMANTI, SUMATERA BARAT, INDONESIA - Nopriansyah, Beri; Nilna Aldzakhiroh; Neli Asmaniah; Khuntum khaira ummah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Instructional media are a key element in supporting the success of the learning process, particularly in enhancing students’ motivation to learn Arabic. However, the use of limited media, such as blackboards, tends to make students bored, passive, and unmotivated during lessons. This study aims to analyze the effect of implementing strip story media on improving students’ motivation to learn Arabic at SMP N 1 Hiliran Gumanti, West Sumatra. The method used was an experiment with a quasi-experimental design involving two classes: Class VIII 1 as the control group and Class VIII 3 as the experimental group. Data analysis techniques included descriptive statistics, homogeneity tests, and hypothesis testing. The results showed that the use of strip story media had a significant effect on students’ learning motivation, with a significance value of 0.000 (<0.05), thus accepting Ha and rejecting H0. Additionally, there was an increase in the average student learning motivation from 24.48 (45%) in the “moderate” category to 39.85 (75%) in the “high” category. Thus, the strip story medium proved effective in enhancing students’ motivation to learn Arabic.